Furin Processing and Proteolytic Activation of Semliki Forest Virus - Zhang, Xinyong (American Society for Microbiology, 2003)
The alphavirus Semliki Forest virus (SFV) infects cells via a low-pH-dependent membrane fusion reaction mediated by the E1 envelope protein. Fusion is regulated by the interaction of E1 with the receptor-binding protein E2. E2 is synthesized as a precursor termed “p62,” which forms a stable heterodimer with E1 and is processed late in the secretory pathway by a cellular furin-like protease. Once processing to E2 occurs, the E1/E2 heterodimer is destabilized so that it is more readily dissociated by exposure to low pH, allowing fusion and infection. We have used FD11 cells, a furin-deficient CHO cell line, to characterize the processing of p62 and its role in the control of virus fusion and infection. p62 was not cleaved in FD11 cells and cleavage was restored in FD11 cell transfectants expressing human furin. Studies of unprocessed virus produced in FD11 cells (wt/p62) demonstrated that the p62 protein was efficiently cleaved by purified furin in vitro, without requiring prior exposure to low pH. wt/p62 virus particles were also processed during their endocytic uptake in furin-containing cells, resulting in more efficient virus infection. wt/p62 virus was compared with mutant L, in which p62 cleavage was blocked by mutation of the furin-recognition motif. wt/p62 and mutant L had similar fusion properties, requiring a much lower pH than control virus to trigger fusion and fusogenic E1 conformational changes. However, the in vivo infectivity of mutant L was more strongly inhibited than that of wt/p62, due to additional effects of the mutation on virus-cell binding.